The effects of soil fumigation, applied fertilizers and climate on the growth and nutrient levels of cayenne pineapples under field conditions - Marr, George Stuart (Rhodes University, Faculty of Science, Botany Department, 1973)
From Introduction: The pineapple producing area of the Eastern Cape lies between 33°S and 34°S latitude. It is the most distant area from the equator in which pineapples are grown commercially, most other areas lying between latitudes 25°N and 25°S (Collins, 1960). The prevailing climatic conditions may be considered as being adverse to the growth of a plant which originated in the tropics. Girton, (1962) considers the area to be unsuitable for commercial production because of the cold weather experienced during winter. Seasonal fluctuations in growth and nutrient levels of the plant have been referred to by van Lelyveld, (1964), but these have never been studied locally. Because of the profound effect of temperature on the growth and nutrient requirements of any plant, it was deemed necessary to investigate the effects of the cooler conditions on the growth and nutrient levels of the pineapple plant, the results of which may give some indications of seasonal nutrient requirements.
Keywords: Uncatalogued